Microporous electrostrictive materials for vibrational energy harvesting. Issue 1 (28th August 2018) - Pruvost, Mickaël; Smit, Wilbert J; Monteux, Cécile; Poulin, Philippe; Colin, Annie
Abstract: We present electrostrictive materials with excellent properties for vibrational energy harvesting applications. The developed materials consist of a porous carbon black composite, which is processed using water-in-oil emulsions. In combination with an insulating layer, the investigated structures exhibit a high effective relative dielectric permittivity (up to 182 at 100 Hz) with very low effective conductivity (down to 2.53 10 −8 S m −1 ). They can generate electrical energy in response to mechanical vibrations with a power density of 0.38 W m −3 under an applied bias electric field of 32 V. They display figures or merit for energy harvesting applications well above reference polymer materials in the field, including fluorinated co- and ter-polymers synthetized by heavy chemical processes. The production process of the present materials is based on non hazardous and low-cost chemicals. The soft dielectric materials are highly flexible (Young's modulus of ∼1 MPa) making them also suited for highly sensitive capacitive sensors.